2016
DOI: 10.1097/ncq.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Pediatric Readmissions

Abstract: The authors describe a quality improvement initiative aimed at decreasing unplanned 7- and 30-day readmission rates in an urban, pediatric, tertiary care hospital. A stepwise approach was used to disseminate the pilot initiative across 16 inpatient units. Use of a teach-back methodology combined with a discharge bundle resulted in an 8% reduction in 7-day readmission and 10% reduction in 30-day readmission over 16 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…By gradually implementing this over 16 inpatient units, they were able to decrease readmissions by 8% at 7 days and 10% at 30 days. Similar to our study, in the study by Shermont et al, 9 multiple small tests of change were used to gradually implement their improvement strategy and obtain a significant decrease in their outcomes measure.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…By gradually implementing this over 16 inpatient units, they were able to decrease readmissions by 8% at 7 days and 10% at 30 days. Similar to our study, in the study by Shermont et al, 9 multiple small tests of change were used to gradually implement their improvement strategy and obtain a significant decrease in their outcomes measure.…”
Section: Discussionmentioning
confidence: 58%
“…8 Although these were the first studies to look at unplanned readmission to the hospital system following pediatric surgery, none of them focused on measures to reduce these rates. Shermont et al 9 focused on standardization of discharge bundles combined with teach back methodologies to improve the rate of 7-day and 30-day readmissions following discharge from a pediatric hospital. They used PDSA cycles to implement a standardized discharge plan including medication reconciliation, scheduled follow-up appointments, and verifying that the patient/family understood the discharge plan and a number to call for any questions or concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of ePED in hospitals with different acuity levels of pediatric care or without Magnet status may result in wider variability of discharge teaching scores. Optimizing the patient/family experience (Shermont, Pignataro, Humphrey, & Bukoye, 2016;Wood et al, 2017) is a priority for healthcare systems in the current era of performance measurement and value-based care, yet nurses often feel unprepared to teach (Lahl, Modic, & Siedlecki, 2013). Having the ePED app available to facilitate discharge teaching provides a structure to assist the nurse in applying evidence-based teaching strategies that promotes the nurse's confidence as an effective teacher.…”
Section: Discussionmentioning
confidence: 99%
“…1 Researchers reported families identified that feeling unprepared for discharge contributed to a return to the emergency department (ED). 1,2 When a discharged patient returns to the ED, these visits can be complicated by a readmission to the hospital. Patients and their families can experience effects of hospital resource reutilization due to inpatient readmission, including financial and/or psychosocial suffering from lost work revenue, high health care costs, and disruption in family relationships.…”
mentioning
confidence: 99%